The Effect Of Trichoderma Sp. and Kinds Of Fertilizer costs on Growth and Production Green Mustard (Brasicca Rapa L.) - Alan Aziz N.W; Abdul Wachid (Nabatia, 2019)
This research aims to determine the effect of Trichoderma sp. and kinds of manure on growth and production of green mustard greens. This research was conducted in Sawocangkring Village, Wonoayu Subdistrict, Sidoarjo Regency with land height 5 meter above sea level. This research was factorially prepared in a randomized block design (RAK) with two factors and repeated three times. The first factor is the appli- cation of Trichoderma sp. Consists of: without Trichoderma sp., Trichoderma sp. isolates Tc-Jjr-02, and Trichoderma sp. isolate Tc-Pjn-01. The second factor is the kind of manure consisting of: without fertilizer, chicken manure, cow manure. Variables observed: plant length, number of leaves, stem diameter, wet weight and dry weight of plant stems, wet weight and root dry weight, indexpanen. The data obtained from this study were ana- lyzed statistically by using analysis of variance (ANOVA), followed by the test of honest difference (BNJ) with 5% level. The results showed there is a interaction effect between the application of Trichoderma sp. and manure type to plant length, number of leaves, and stem diameter. The best treatment is treated without Trichoderma sp. (control) and chicken manure (T0P1) resulted in plant length 25,77 cm, leaf number 9 leaf, stem diam- eter 0,69 cm, wet weight of plant stover 34,03 gr, dry weight of plant stem 8.10 gr, wet root weight 1.67 gr, dry weight of roots 0.77 gr, and harvest index 0.89.